The Use of Statistical Methods to Evaluate the Quality of Finishing of Building Products and Construction - Loganina, V. I.; Uchaeva, T. V. (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
The purpose of the work is to develop recommendations for ensuring the quality of paints and varnishes for building products and structures. Information is provided on the application of statistical methods for managing the quality of products when painting building products and structures. It is shown, that the quality of the finish depends on the method of applying the paint, the porosity of the cement substrate. The problem of safety of paint and varnish coating properties during storage and operation is significant and relevant. For coatings based on all types of paints the minimum roughness value of the coating surface and the minimum value of the risk are typical in the case of applying paints to the putty surface, regardless of the method of application. Offered to organizations, firms, engaged in the execution of finishing works, the introduction of the kaizen approach to the renewal of staining technology, based on continuous improvement of activities and providing for the use of statistical methods for managing the quality of products. Information on the effect on the longevity of coatings of the quality of their appearance is given. It is shown, that coatings with a high roughness index are characterized by low durability during exploitation. A model of the cohesive strength of coatings is presented, depending on the surface roughness.